A comprehensive exergy analysis of a prototype Peltier air-cooler; experimental investigation. (February 2019) - Sadighi Dizaji, Hamed; Jafarmadar, Samad; Khalilarya, Shahram; Pourhedayat, Samira
Abstract: Thermoelectric coolers have been abundantly investigated from the viewpoint of the first law of thermodynamic. However, extremely few exergy analysis have been probed for thermoelectric air-coolers. Because of the importance of exergy consideration in each thermodynamic process, this paper experimentally focuses on the effect of various parameters on exergy destruction and the second law performance through a thermoelectric air cooler. The effects of flow and thermodynamic parameters including air flow rate, incoming air temperature, water flow rate, incoming water temperature, DC voltage/ampere etc. on exergetic characteristics are clarified in this study. Interesting meaningful curve behavior was observed for exergetic performance of thermoelectric cooler. Indeed, curve behavior of exergetic performance is descending-ascending and therefore a critical value of DC voltage was found in which the amount of second law performance has a minimum/maximum value. Increment of air flow rate improved the exergetic performance of Peltier-air cooler. Besides, higher air inlet temperature reduced exergy destruction of thermoelectric module (TEM) which means that Peltier air cooler is appropriate for regions with warmer weather in comparison with moderate climates. Highlights: A prototype Peltier air cooler was designed and fabricated. The effects of air and water parameters on exergetic characteristics are studied. The effect of DC voltage/current on exergy destruction and exergy performance are analyzed. Notable curves behavior were observed for exergy characteristics of Peltier cooler.